Plakat "Sicher Velofahren in der Stadt! Velo-Initiative JA" - Rothacher, Andreas
Verkehr;Organisation des Verkehrs (allgemein);Organisation des Verkehrs (speziell);Personenverkehr;Verkehrsteilnehmer/in;Radfahrer/in Verkehr;Landverkehr;Strassenverkehr;Zweiradfahrzeug;Velo Verkehr;Verkehrspolitik (allgemein);Verkehrspolitik (speziell);Verkehrssicherheit Verkehr;Landverkehr